A model to account for variations in production in southern Spain - García-mozo, Herminia; Dominguez-vilches, Eugenio; Galán, Carmen (Annals of Agricultural and Environmental Medicine, 2012)
One of the characteristics of holm-oak acorn production is its high variability among individuals and years. To examine the main causes of this fact, a study was conducted from 1998-2010 in a natural area of holm-oak in southern Spain, where floral phenology, fruit production, fruit size, airborne pollen emission and meteorology factors were analyzed with the ultimate aim of developing a model for forecasting holm-oak yield. Pollen emission during flowering season was the main factor determining the final acorn harvest, but also some meteorological variables played an important role in explaining acorn crop variations, especially humidity and temperature during the months of April and September. The reliability of the proposed model was externally validated using data not included in its construction; validation yielded acceptable results, with a minimum error of estimation. Our results appear to be very useful for planning cropping and pig feeding strategies. Further research could extend the use of airborne pollen counts in forest studies relating to anemophilous species, in order to optimize agricultural policies.
Keywords: acorn production; Aerobiology; Holm oak; model; oak forest; Phenology; pollen; quercus ilex subsp. ballota

Catkin frost damage in Mediterranean cork-oak (Quercus suber L.). (Israel Journal of Plant Sciences, 2001)
During a period of study of floral phenology and pollen production in the cork-oak, Quercus suber L. (199799), an interruption of catkin development was detected in spring 1998. The cause might have been a sharp drop in minimum temperatures during that period, which coincided with the initial stages of microsporogenesis. Results show that environmental temperatures close to 0 ºC halted microsporogenesis and catkinelongation, resulting in their complete death. No fruits were observed in the affected zone, as a possible consequence of the lack of pollen. Phenological, histological, andaerobiological data are analyzed as a whole in order to gain a better understanding of the phenomenon. Cold spells during flowering may be one of the factors influencing the high interannual variability of acorn production in Quercus species. [ABSTRACT FROM AUTHOR]

Catkin frost damage in Mediterranean cork-oak (Quercus suber L.). - García-mozo, Herminia; Hidalgo, Pablo J.; Galán, Carmen; Gómez-Casero, Maria Teresa; Domínguez, Eugenio (Israel Journal of Plant Sciences, 2001)
During a period of study of floral phenology and pollen production in the cork-oak, Quercus suber L. (199799), an interruption of catkin development was detected in spring 1998. The cause might have been a sharp drop in minimum temperatures during that period, which coincided with the initial stages of microsporogenesis. Results show that environmental temperatures close to 0 ºC halted microsporogenesis and catkinelongation, resulting in their complete death. No fruits were observed in the affected zone, as a possible consequence of the lack of pollen. Phenological, histological, andaerobiological data are analyzed as a whole in order to gain a better understanding of the phenomenon. Cold spells during flowering may be one of the factors influencing the high interannual variability of acorn production in Quercus species. [ABSTRACT FROM AUTHOR]
Keywords: CATKIN-bearing plants; Cork oak; flowers; Fruit; Phenology; PLANT spores; POLLEN (citation)